Central Sensitization in Neurological, Psychiatric, and Pain Disorders: A Multicenter Case-Controlled Study - Keisuke Suzuki; Yasuo Haruyama; Gen Kobashi; Toshimi Sairenchi; Koji Uchiyama; Shigeki Yamaguchi; Koichi Hirata (Pain Research and Management)
Background. The role of central sensitization in refractory pain-related diseases has not yet been clarified. Methods. We performed a multicenter case-controlled study including 551 patients with various neurological, psychological, and pain disorders and 5,188 healthy controls to investigate the impact of central sensitization in these patients. Symptoms related to central sensitization syndrome (CSS) were assessed by the Central Sensitization Inventory (CSI) parts A and B. Patients were categorized into 5 groups based on CSI-A scores from subclinical to extreme. The Brief Pain Inventory (BPI), addressing pain severity and pain interference with daily activities, and the Patient Health Questionnaire (PHQ)-9, assessing depressive symptoms, were also administered. Results. CSI-A scores and CSI-B disease numbers were significantly greater in patients than in controls (p<0.001). Medium effect sizes (r = 0.37) for CSI-A scores and large effect sizes (r = 0.64) for CSI-B disease numbers were found between patients and control groups. Compared with the CSI-A subclinical group, the CSI-A mild, moderate, severe, and extreme groups had significantly higher BPI pain interference and severity scores, PHQ-9 scores, and CSS-related disease numbers based on ANCOVA. Greater CSI-B numbers resulted in higher CSI-A scores (p<0.001) and a higher odds ratio (p for trend <0.001). CSS-related symptoms were associated with pain severity, pain interference with daily activities, and depressive symptoms in various pain-related diseases. Conclusions. Our findings suggest that CSS may participate in these conditions as common pathophysiology.